The Effect of Inhaled Lemon Essential Oil Aromatherapy on Pain Intensity in Women During the Active Phase of the First Stage of Labor at Pesanggrahan Regional General Hospital in 2025 - ‎, Rosita; Nuurjanah, Febri Annisa; Jayanti, Christin (JOURNAL EDUCATIONAL OF NURSING(JEN), 2025)
Labor pain is a subjective experience encountered by more than 90% of women worldwide, with intensity ranging from moderate to severe. At Pesanggrahan Regional General Hospital, pain management remains largely conventional and has not yet systematically incorporated complementary therapies. Lemon aromatherapy contains limonene compounds that exert analgesic and relaxation effects through stimulation of the limbic system, thereby reducing pain perception. This study aimed to determine the effect of inhaled lemon essential oil aromatherapy on pain intensity in women during the active phase of the first stage of labor at Pesanggrahan Regional General Hospital in 2025.This study employed a quasi-experimental design using a one-group pretest–posttest approach. The population consisted of women in the active phase of the first stage of labor at Pesanggrahan Regional General Hospital, with a total sample of 32 respondents selected through purposive sampling. The research instrument was an observation sheet using the Wong-Baker Faces Pain Rating Scale. Data were analyzed using the Paired Sample t-test.The results showed that prior to the intervention (pretest), the majority of respondents experienced severe pain, with a pain scale score of 8 (25.8%). After receiving inhaled lemon aromatherapy (posttest), pain intensity decreased, with most respondents reporting pain scores of 3 and 4 (each 19.4%). Statistical analysis revealed a p-value of 0.000 (p < 0.05), with a mean reduction in pain intensity of 3.5806. It can be concluded that inhaled lemon essential oil aromatherapy has a significant effect on reducing pain intensity in women during the active phase of the first stage of labor at Pesanggrahan Regional General Hospital in 2025. This therapy may serve as a safe and effective non-pharmacological alternative for pain management in the delivery room